MENDESKRIPSIKAN TENTANG BIMBINGAN BELAJAR BAGI PESERTA DIDIK SD NEGERI WOLIBANG - Intan Permatasari Lema Madde; Lisa Viktoria Malimou, Loriance Tonu Weni, Yessy Mata, Petrus Mau Tellu Dony (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study is to describe the implementation of tutoring at Wolibang Public Elementary School, especially in Grade 1. This study uses Observation and Interview Methods with a descriptive qualitative approach. This study was conducted at Wolibang Public Elementary School. The informants in this interview were the Grade 1 Homeroom Teachers of Wolibang Public Elementary School. The results of this study indicate that tutoring is implemented in a structured manner in the form of individual and small group activities. The strategies used by teachers include personal and contextual approaches. Obstacles faced include limited time, facilities, and parental support. Nevertheless, students show significant improvements in basic academic skills such as reading and writing. This study emphasizes the importance of tutoring as an integral part of the basic education process.